Волшебное слово: рассказы / В. А. Осеева - Осеева Валентина Александровна (Школьная библиотека, 2012)
Экземпляры: М/а ДБ (20130117) / Инвентарный номер: 99249 / Цена: 100.00 / Авт.знак: О-72 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6